Gender, sexuality, and childhood: academic production in debate - Fernandez, Cristiane Bonfim; Martins, Eunice Emanuelle Soares (Argumentum, 2023)
This article analyses how the themes of the gender and sexuality of children and adolescents were discussed/conceived in the scientific output of periodicals in the area of Social Work between 2011 and 2020. A survey of articles on the Portal de Periódicos da Capes was carried out based on the descriptors, gender, sexuality, children, adolescents and childhood, 54 articles in Portuguese were mapped, and from these 10 were selected for analysis. The studied works were mainly centred in the Southeast and South regions, from the journal Qualis, editions B1 and B2, whose authors are primarily linked to university academic institutions. Most demonstrate a criticism of the strictly biological bias of child sexuality and gender, as their authors understand this issue as a historical-cultural construction. It concludes that there are still little output on the subject, but that there has, nevertheless, been a significant increase from 2019 to 2020.Keywords: Gender. Sexuality. Child. Adolescent. Academic output.